Formation of the intellectual systems for the territorial development of land administration in the coastal regions - Bieliatynskyi, Andrii; Mingming, Wen; Chang, Liu; Mamonov, Kostyantyn; Dymchenko, Olena (Journal of Environmental Engineering and Landscape Management, 2022)
It is essential to create the quantitative basis for decision taking on increasing the efficiency of land administration in the coastal regions as an important factor of ensuring development at the regional level. The analysis of the existing scientific research showed lack of unity in theoretical and methodological approaches to defining the territorial development of land administration in the coastal regions, which has been characterized as a combination of spatial, urban planning, investment and environmental factors, the interrelation of which results in achieving a new condition of land management compared to the past, accounting for the social, institutional, managerial peculiarities and the level of communication between the stakeholders operating in the field of land administration in the regions.